Recellularized bovine pericardium with autologous mesenchymal stem cells reduces immune activation. (13th September 2022) - Bozso, Sabin J.; Kang, Jimmy J. H.; EL‐Andari, Ryaan; Boe, Dana; Hedtke, Hannah; Moon, Michael C.; Freed, Darren H.; Nagendran, Jayan; Nagendran, Jeevan
Abstract: Introduction: Current bioprosthetic heart valve replacement options are limited by structural valvular deterioration (SVD) due to an immune response to the xenogenic scaffold. Autologous mesenchymal stem cell (MSC) recellularization is a method of concealing xenogenic scaffolds, preventing recipient immune recognition of xenogenic tissue heart valves, and potentially leading to reduction in SVD incidence. The purpose of this study is to examine the effects of autologous MSC recellularized tissue on the immune response of human whole blood to bovine pericardium (BP). We hypothesized that autologous MSC recellularization of BP will result in reduced pro‐inflammatory cytokine production equivalent to autologous human pericardium. Methods: Bone marrow, human pericardium, and whole blood were collected from adult patients undergoing elective cardiac surgery. Decellularized BP underwent recellularization with autologous MSCs, followed by co‐incubation with autologous whole blood. Immunohistochemical, microscopic, and quantitative immune analysis approaches were used. Results: We demonstrated that native BP, exposed to human whole blood, results in significant TNF‐α and IL1β production. When decellularized BP is recellularized with autologous MSCs and exposed to whole blood, there is a significant reduction in TNF‐α and IL1β production. Importantly, recellularized BP exposed to whole blood had similar production of TNF‐α and IL1β when compared to autologous human pericardium exposed to human whole blood. Conclusion: Our results suggest that preventing initial immune activation with autologous MSC recellularization may be an effective approach to decrease the recipient immune response, preventing recipient immune recognition of xenogeneic tissue engineered heart valves, and potentially leading to reduction in SVD incidence.